Verbs from the Inflection Critic in ALSAHAH - YOUNIS, BATOOL FARHAN; ALFAHHAM, SAFAA TAWFEEQ KADHIM (Al-Adab Journal, 2021)
My desire directed to study inflection (Morphological) critics as extracted research. Because this level of linguistic research levels, it is interesting with utmost benefit, functional tasks were linked to build the word. They are interrelated, interconnected with topics of voice, grammar studies, attempting to arrive to perfect morphological textbook. It is close to mind of receipt, to present concepts, smooth structure theories to move acceleration of research progress I have searched many of critic examples of verbs in SAHAH ALJAWAHERY with study, analysis and critic after classify them. And after start to state analysis of ALJAWAHERY critically for them, to elucidate articulation of its linguistic using and to state its correctness and mistake. To link that with meaning, motions of the verb which determine its weight and category and I divided the abstract as following: (Motion of AYEN of the verb in the past, Motion of AYEN of the verb in the present, the last reasoned part, Stripped and extra, Place invert)